Asymmetric transmission of a planar metamaterial induced by symmetry breaking. (21st February 2018) - Bai, Yu; Chen, Yuyan; Zhang, Yongyuan; Wang, Yongkai; Aba, Tudahong; Li, Hui; Wang, Li; Zhang, Zhongyue
Abstract: Asymmetric transmission (AT) is widely used in polarization transformers and polarization-controlled devices. In this paper, a planar metamaterial nanostructure with connected gammadion-shaped nanostructure (CGN) is proposed to achieve AT effect for forward and backward propagations of circular polarized light. The CGN arrays can produce magnetic moment oscillation that is normal to the metamaterial plane, which is weakly coupled to free space and generates transmission valleys. The introduction of symmetry breaking exerts a strong influence on the AT effects, and these effects can be tuned by the structural parameters. Our planar metamaterials may have potential for application in the future design of polarization-controlling devices.